A cultura nacional na arte, na linguagem e na música: percepções políticas e estéticas nas crônicas de Mário de Andrade (1933 1941) - Jeronimo, Laiane Fernandes (2014)
This text entitled The national culture in Arts, Language and Music: political and aesthetic in chronic Mário de Andrade (1933 - 1941) aims to discuss perceptions of the relationship between modernism and nationalism in the work of Mario de Andrade, especially in his chronicle. To achieve this goal we set out some issues between them that the writing of chronic marks a distinct perspective view of Mário de Andrade on the national. Another issue relates to the treatment given by Andrade to cultural themes such as art, language and music discussed in the perspective of its Brazilian characteristics. In this sense, we raised the hypothesis that for Andrade understand nationalism is not a territorial, economic and political issue, but, above all, cultural. Thus, in the first chapter, entitled On Chronicles, Nationalism and Mário de Andrade, we propose to reflect the chronicle and its singularities, that allow so we take as a relevant document for historiographical studies, such as present in this dissertation. Address we will also, in this chapter, on a discussion of nationalism and how literature was central to the discussions on the nation and finally, we bring a brief intellectual history of Mário de Andrade, raising important question of your life and work and begin the debate about the issues of national culture and nationalism are present in his chronicles. In the second chapter, Art, Language and Memory under the eyes and pen of Mario de Andrade, we will address how language and the language are presented in the chronicles, the importance of memory and preserve the same for the construction of national identity and how the author perceives as an instrument of his nationalist ideas. In the third chapter, entitled The National Music in chronic Mário de Andrade, discuss how the national music is treated in his chronicles and as the author inserts this artistic manifestation of nationalism in your project.